1999
DOI: 10.1074/jbc.274.34.24059
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Induces Activation and Formation of Stat4 and Stat1-Stat2 Complexes in Human Vascular Smooth Muscle Cells

Abstract: Urokinase-type plasminogen activator (uPA) and its specific receptor (uPAR) act in concert to stimulate cytoplasmic signaling machinery and transcription factors responsible for cell migration and proliferation. Recently we demonstrated that uPA activates the Janus kinase/signal transducers and activators of transcription (Stat1) signaling in human vascular smooth muscle and endothelial cells. However, the important question whether other transcription factors of the Stat family, in addition to Stat1, are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…Furthermore, we did not observe activation of the IFN-related Janus kinase͞STAT (JAK͞STAT) pathway of signal transduction (36), as reported for smooth muscle cells treated with pro-uPA (37), that we have correlated to the anti-HIV effect of IFNs in U937 cells (ref. 38, and data not shown).…”
Section: Suppression Of Pma-induced Hiv Expression In U1 Cells By Prosupporting
confidence: 81%
“…Furthermore, we did not observe activation of the IFN-related Janus kinase͞STAT (JAK͞STAT) pathway of signal transduction (36), as reported for smooth muscle cells treated with pro-uPA (37), that we have correlated to the anti-HIV effect of IFNs in U937 cells (ref. 38, and data not shown).…”
Section: Suppression Of Pma-induced Hiv Expression In U1 Cells By Prosupporting
confidence: 81%
“…However, until recently, Stat2 was known to be activated only by the IFN-␣/␤ pathway, restricting a general test of this hypothesis. A recent report has shown that the urokinase receptor, expressed by human vascular smooth muscle cells, also activates Stat2, and that indeed Stat4 is also activated in response to urokinase signaling (36). This observation supports the idea that human Stat2 is involved in Stat4 recruitment and activation.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to their direct involvement in the proteolytic (uPAR) and adhesive properties of cells, both pro-uPA (Gudewicz and Bilboa, 1987; Boyle et Fibbi et al, 1988;Del Rosso et al, 1992;Resnati et al, 1996;Gyetko et al, 1996;Degryse et al, 1999) and VN (Yebra et al, 1996;Kjùller et al, 1997;Stahl and Mueller, 1997;Carriero et al, 1999; directly stimulate cell migration. The interaction of uPAR with several integrins and the modulation of their function is an established fact; for example, the presence and the level of uPAR a ects the choice between adhesion on ®bronectin v. vitronectin, the internalization of ®brinogen or even the constitutive activation of MAP-K in certain cancer cells leading to cell proliferation Simon et al, 1996;Xue et al, 1997;Dumler et al, 1999;Aguirre Ghiso et al, 1999;Kusch et al, 2000). Direct interactions of uPAR with integrins has been shown by several techniques, including¯uorescence resonance energy transfer and co-immuno-precipitation (Bohuslav et al, 1995;Wei et al, 1996;Yebra et al, 1996;Xue et al, 1997;Carriero et al, 1999Simon et al, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Migration responses are generally observed at low (physiological) levels of uPAR expression, while proliferation responses may require higher levels as observed in cancer cells (Aguirre Ghiso et al, 1999;Ossowski and Aguirre Ghiso, 2000;Webb et al, 2000). Several signal transducing molecules have been identi®ed (Konakova et al, 1998;Webb et al, 2000;Degryse et al, 1999;Dumler et al, 1999).…”
Section: Introductionmentioning
confidence: 99%